Effects of Corticobasal Implant Protrusion inside the Nasal and Maxillary Sinus - Awadalkreem, Fadia (Ann Maxillofac Surg, 2020)
BACKGROUND: Implant protrusion into the nasal and maxillary sinuses presents a challenge in cases of severely resorbed maxillae. AIM: The aim of this study was to evaluate the clinical and radiographic effects of BECES(®) implant penetration depth into the nasal and maxillary sinuses. SETTING AND DESIGN: This was an observational study conducted in a tertiary institution. MATERIALS AND METHODS: Forty-nine BECES(®) implants were inserted into the maxilla of patients who presented with severely resorbed ridges but no history of sinusitis. Forty-five implants protruded into the sinus cavities. Patients were examined clinically and radiographically at 1 week and 3, 6, 12, and 18 months after insertion. Maxillary sinus health, survival and success rates, and peri-implant health were assessed using the plaque index (PI), calculus index, modified gingival index (MGI), and probing pocket depth (PPD). STATISTICAL ANALYSIS: Wilcoxon signed-rank test and Mann–Whitney test were used in this study. RESULTS: Four (8.16%) of the 45 implants that penetrated the cavities reached the sinus floor without disrupting the membrane; the penetration depth was ≥4 mm in 20 implants (44.44%) and <4 mm in 25 (55.56%). No patient showed clinical or radiographic signs of sinusitis during the observation period. There were significant differences in the PI, MGI, and PPD values between baseline and the 18-month follow-up with no association with the penetration depth. All implants showed radiographically direct bone-to-implant contact. Where the implant tip barely reached the sinus floor, the membrane healed uneventfully while when deeply penetrating the sinus, the membrane healed around the implant but did not cover the tip. All prostheses and implants survived during the observation period. CONCLUSION: Penetration depth of polished implants with cortical engagement into the maxillary sinus or the floor of the nose does not negatively affect implant survival, the success rate of the treatment, nor peri-implant soft-tissue health. It also does not provoke the development of sinusitis.